Pre-service teachers' preparedness for classroom teaching: an investigation of teacher education program transferability and connection to ESL Classroom / Abang Fhaeizdhyall Abang Madaud - Abang Madaud, Abang Fhaeizdhyall (2015)
The major purpose of this study is to investigate to what extent do pre-service teachers apply the methods, theory, and training received during years of training in the teacher training program into their classroom teaching. Additionally, this study also examines the perceptions of pre-service teachers’ supervisors of their supervisees’ preparedness to enter the real world of teaching by analyzing their teaching ability in terms of content, pedagogical and grammar knowledge. Five interrelated research questions were formulated to guide the study; (1) What are the specific aspects of the teacher education program that helped the pre-service teachers during their teaching practicum?; (2) What are the difficulties and challenges faced by the pre-service teachers in the program and how to overcome them?; (3) How prepared are the pre-service teachers to teach English?; (4) To what extent are the strengths and weaknesses of the pre-service teachers as perceived by the university supervisors?; (5) What are the suggestions and recommendations by the trainees to better improve the current teacher education program? The sample involved in the study were pre-service teachers from the Bachelor in Education TESL program who had just completed their 3-month teaching practicum and are currently in the final semester. In addition, the university supervisors were also selected to be included as the participants of the study to answer research question number four. This study employed a qualitative research design and the data sources included pre-service teacher questionnaires and interviews, document analysis, and university supervisor interviews. The questionnaire distribution phase was conducted with 68 pre-service teachers who came for a one-day post mortem of their teaching practicum. Subsequently, interview sessions were conducted with 7 of the respondents afterwards. To gain better insight of the issues in teacher preparation program, interview with 5 university supervisors were also conducted. The findings of this study revealed significant courses such as ethodology courses and classroom management, theories in language learning, drama project, and microteaching experience as the important aspects that contributed to the trainees’ preparedness to teach. Additionally, the trainees also stated the challenges they faced in the program are in terms of dealing with the school students, their self-belief, the role of the supervisors and school related issues. Overall perceived preparedness to teach shows that the pre-service teachers perceived themselves as moderately prepared to teach which was similar to their supervisors’ perceptions. This study also revealed some strengths and weaknesses of the trainees in terms of grammatical knowledge, content knowledge and effectiveness in teaching, in which the supervisors have also provided some suggestions to address them. To conclude, the trainees offer some suggestions for improvement of the current teacher education program in terms of developing trainees’ teaching experience, courses amendment, authentic school experience, and removal of some less significant courses.